Perancangan Sistem Informasi Surat Menyurat Pada Sekolah Dasar Dikampungbaru Berbasis Website - Ike Susilowati; Budiman Budiman; Izzatul Umami (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
This study aims to develop system performance in Junior School agenciesin terms of correspondenceadministration, in this digital era, it should be madea system that helps human daily work in termsof filing documents, archives and filesvarious other forms of digital data, this research test will bebased on the effectivenessthe system, in terms of data collection and features made so that it canbecome a website applicationwhich is easy to use. This study also aims to test the effective validation of the application by interviewto users of the application, so as to produce suggestions and criticism so that in the future,This research can be further developed into an mobile application and user friendly.